2018
DOI: 10.1186/s41687-018-0084-z
|View full text |Cite
|
Sign up to set email alerts
|

Impact of short stature on health-related quality of life in long-term survivors of acute lymphoblastic leukemia in childhood and adolescence

Abstract: PurposeSome survivors of acute lymphoblastic leukemia (ALL) in childhood and adolescence exhibit short stature, especially if their treatment included cranial irradiation. The impact of this outcome on health-related quality of life (HRQL) is uncertain and so formed the basis for the investigation reported here.MethodsThis study examined the association between self-reported HRQL and measured height in a cohort (n = 75) of survivors of ALL more than 10 years from diagnosis. HRQL was expressed as utility scores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
1
0
0
Order By: Relevance
“…In our study, weight and BMI in children with ALL did not differ from their healthy peers; however, reduced height was observed. This finding is consistent with previous studies 22,24‐27 that reported a decrease in height during the period from diagnosis until the end of therapy as one of the negative sequelae of chemotherapeutic treatment that was observed in children diagnosed with ALL in early childhood. The first decrease in height was detected six months after the beginning of treatment, which may affect the final height after completion of therapy 22,24 .…”
Section: Discussionsupporting
confidence: 93%
“…In our study, weight and BMI in children with ALL did not differ from their healthy peers; however, reduced height was observed. This finding is consistent with previous studies 22,24‐27 that reported a decrease in height during the period from diagnosis until the end of therapy as one of the negative sequelae of chemotherapeutic treatment that was observed in children diagnosed with ALL in early childhood. The first decrease in height was detected six months after the beginning of treatment, which may affect the final height after completion of therapy 22,24 .…”
Section: Discussionsupporting
confidence: 93%